Eyelid ptosis from sympathetic nerve dysfunction mistaken as myopathy: a simple test to identify this condition. Issue 6 (7th February 2007) - Tomelleri, G; Vattemi, G; Filosto, M; Tonin, P
Abstract : Acquired isolated unilateral or bilateral blepharoptosis has many aetiologies. When the pupils are normal, a myasthenic syndrome or myopathy has to be ruled out. If the tests for myasthenia gravis are negative, the next step is to perform a muscle biopsy to establish a diagnosis. Muscle examination may show a mitochondrial disorder, non-specific abnormalities or be quite normal. We identified three patients, who had previously undergone various investigations, including a muscle biopsy, whose lid ptosis disappeared using eye drops containing naphazoline nitrate, a sympathomimetic drug, thus suggesting partial Horner's syndrome. We emphasise the usefulness of this simple and cheap test before performing more traumatic and expensive investigations.